Mechanisms Underlying Graft Union Formation and Rootstock Scion Interaction in Horticultural Plants - Rasool, Aatifa; Mansoor, Sheikh; Bhat, K. M.; Hassan, G. I.; Baba, Tawseef Rehman; Alyemeni, Mohammed Nasser; Alsahli, Abdulaziz Abdullah; El-Serehy, Hamed A.; Paray, Bilal Ahmad; Ahmad, Parvaiz (Frontiers in Plant Science, 2020)
Grafting is a common practice for vegetative propagation and trait improvement in horticultural plants. A general prerequisite for successful grafting and long term survival of grafted plants is taxonomic proximity between the root stock and scion. For the success of a grafting operation, rootstock and scion should essentially be closely related. Interaction between the rootstock and scion involves complex physiological-biochemical and molecular mechanisms. Successful graft union formation involves a series of steps viz., lining up of vascular cambium, generation of a wound healing response, callus bridge formation, followed by vascular cambium formation and subsequent formation of the secondary xylem and phloem. For grafted trees compatibility between the rootstock/scion is the most essential factor for their better performance and longevity. Graft incompatibility occurs on account of a number of factors including of unfavorable physiological responses across the graft union, transmission of virus or phytoplasma and anatomical deformities of vascular tissue at the graft junction. In order to avoid the incompatibility problems, it is important to predict the same at an early stage. Phytohormones, especially auxins regulate key events in graft union formation between the rootstock and scion, while others function to facilitate the signaling pathways. Transport of macro as well as micro molecules across long distances results in phenotypic variation shown by grafted plants, therefore grafting can be used to determine the pattern and rate of recurrence of this transport. A better understanding of rootstock scion interactions, endogenous growth substances, soil or climatic factors needs to be studied, which would facilitate efficient selection and use of rootstocks in the future. Protein, hormones, mRNA and small RNA transport across the junction is currently emerging as an important mechanism which controls the stock/scion communication and simultaneously may play a crucial role in understanding the physiology of grafting more precisely. This review provides an understanding of the physiological, biochemical and molecular basis underlying grafting with special reference to horticultural plants.